Pole-Vaulting: Identification of the pole local bending rigidities by an updating technique - Morlier, J.; Mesnard, M.; Cid, M. (Journal of Applied Biomechanics, 2008)
The development of composite material poles since 1960 has played a prominent part in performance improvement in pole-vaulting. Previous studies devoted to pole-vaulting models were based on constant mechanical characteristics. It is thus necessary to identify the local bending rigidities of the pole to build realistic pole-vaulting models. Updating methods developed for dynamic structure studies allow us to describe local mechanical characteristics. These methods are based on the comparison between experimental results and those determined numerically by finite element models. This study presents an adaptation of these methods to determine the local bending rigidities of the pole. The updating technique is validated by a deflection test of a homogeneous beam. Then, a study of the model sensitivity is carried out to investigate the procedure robustness. Finally, the updating method is applied to an old design pole and to a recent one. The results obtained vary greatly from one pole to the other; they highlight the evolutions in pole design.